Analisis Pengaruh Pertumbuhan Tabungan, Deposito, dan Kredit terhadap Pertumbuhan Profitabilitas PT. BPR Kredit Mandiri Indonesia - Winda Dwi Yanthi (Journal Of Resource Management, Economics And Business, 2023)
Purpose: The purpose of this study is to analyze the effect of growth in savings, deposits, and credit on the profitability growth of PT. BPR Kredit Mandiri Indonesia. Research Methodology: This study utilized a quantitative research approach. Data was collected from PT. BPR Kredit Mandiri Indonesia's financial reports and records over a specific period. The primary tools and methods employed in this study include financial ratio analysis, regression analysis, and statistical software for data processing and analysis. Results: The main findings of this study indicate a positive relationship between the growth in savings, deposits, and credit and the profitability growth of PT. BPR Kredit Mandiri Indonesia. The analysis reveals that an increase in savings and deposits leads to higher profitability, as it provides a larger pool of funds for lending and investment activities. Additionally, the growth in credit positively impacts profitability, as it generates interest income and fees for the organization. Limitations: This study has several limitations. Firstly, the analysis is based on secondary data obtained from the financial reports of PT. BPR Kredit Mandiri Indonesia, which may have limitations in terms of accuracy and completeness. Secondly, the study focused solely on the relationship between savings, deposits, credit, and profitability and did not consider other factors that may influence profitability growth. Contribution: This study contributes to the understanding of the factors influencing the profitability growth of PT. BPR Kredit Mandiri Indonesia. The findings can be useful for financial institutions, policymakers, and researchers in the field of banking and finance, providing insights into the importance of savings, deposits, and credit growth in enhancing profitability.